مساهمة تكنولوجيا المعلومات والاتصال في تحسين جودة الخدمات الفندقية دراسة حالة منتجع الغزال الذهبي - السعيد،بن عمر; علي،غريسي; محمود،عشيري (university of eloued جامعة الوادي, 2024)
تهدف هذه الدراسة في مساهمة تكنولوجيا المعلومات والاتصال في تحسين جودة الخدمة الفندقية في المنتجع الغزال الذهبي، وقد تمثلت ابعاد تكنولوجيا المعلومات والاتصال في الأجهزة والبرمجيات، الافراد، قواعد البيانات والشبكات، حيث تم تحليل جودة الخدمة الفندقية الى: الملموسية، الاعتمادية، الاستجابة، الأمان والتعاطف. وتم اعداد استمارة استبيان وزعت على مجموعة من نزلاء في منتجع الغزال الذهبي كدراسة تطبيقية لإسقاط الجانب النظري للدراسة على الواقع الموجود في هذا المنتجع. وقد توصلت الدراسة الى ان مساهمة تكنولوجيا المعلومات من خلال عناصرها الأربعة لها دور فعال في تحسين جودة الخدمات المقدمة من طرف المنتجع. This study aims to investigate the impact of information and communication technology in improving the quality of hotel service in Algerian hotels. Dimensions of information and communication technology are as follows: hardware and software, individuals, databases and networks. The quality of service was also analyzed. Hotel services include: tangibility, reliability, responsiveness, safety and empathy. A s a sample of guests at the Golden Ghazal Hotel was studied as an applied study a to project the theoretical aspect of the study onto the reality existing in Algerian hotels. The results showed the availability of information technology elements and the four connections in the hotel under study. The study also found that there was a contribution for each of the hardware, software, and databases Improving the quality of services provided by the hotel.
مذكرة ماستر علوم تجارية
Keywords: تكنولوجيا المعلومات والاتصال، جودة الخدمة الفندقية، أجهزة وبرمجيات، افراد، شبكات وقواعد البيانات. Keywords: information and communication technology; hotel service quality; hardware and software; individuals; networks and databases.